Strategi Pelatih dalam Meningkatkan Prestasi Atlet Bulutangkis PB Starka di Kabupaten Kerinci - Putra, Fadil Zorif; Saputra, Endarman; Putra, Ceppy Pradana (MAN Insan Cendekia Jambi, 2025)
This research aims to analyze the coach's strategies in improving the performance of badminton athletes at PB Starka in Kerinci Regency. The study employed a qualitative method with a descriptive approach. Research participants consisted of the head coach and badminton athletes from PB Starka, selected using purposive sampling technique. Data collection was conducted through observation, interviews, and documentation, then analyzed using Miles and Huberman's interactive model. The results show that the coach's strategies were developed through three stages: 1) strategy formulation, including initial assessment of athletes' abilities and development of individualized training programs based on age; 2) strategy implementation, covering short-term and long-term training programs, internal and external motivation approaches, and parent-based funding management; 3) strategy control, consisting of evaluation through video recordings and written notes, as well as individualized feedback. Despite facing limitations in facilities and funding, the adaptive strategies implemented by the coach have successfully led athletes to achieve recognition at the provincial level, demonstrating that systematic and individualized approaches in sports coaching can be effective even with limited resources.